2022
DOI: 10.1038/s41467-022-28779-7
|View full text |Cite
|
Sign up to set email alerts
|

α-catenin switches between a slip and an asymmetric catch bond with F-actin to cooperatively regulate cell junction fluidity

Abstract: Abstractα-catenin is a crucial protein at cell junctions that provides connection between the actin cytoskeleton and the cell membrane. At adherens junctions (AJs), α-catenin forms heterodimers with β-catenin that are believed to resist force on F-actin. Outside AJs, α-catenin forms homodimers that regulates F-actin organization and directly connect the cell membrane to the actin cytoskeleton, but their mechanosensitive properties are inherently unknown. By using ultra-fast laser tweezers we found that a singl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 33 publications
(43 reference statements)
3
26
0
Order By: Relevance
“…A plausible explanation for this observation is that the N and/or M domains interfere with cooperative interactions between ABDs, perhaps via interactions with the CTE (Figure 6D). A role for the N-and M-domains in hindering stable binding to F-actin is consistent with optical trap results showing that an α-β-catenin heterodimer forms a transient slip bond with F-actin (< 20 ms) in the absence of any bystanders, but that a longer-lived catch bond is recovered when multiple complexes are present (Arbore et al, 2022).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…A plausible explanation for this observation is that the N and/or M domains interfere with cooperative interactions between ABDs, perhaps via interactions with the CTE (Figure 6D). A role for the N-and M-domains in hindering stable binding to F-actin is consistent with optical trap results showing that an α-β-catenin heterodimer forms a transient slip bond with F-actin (< 20 ms) in the absence of any bystanders, but that a longer-lived catch bond is recovered when multiple complexes are present (Arbore et al, 2022).…”
Section: Discussionsupporting
confidence: 84%
“…Deletion of CTE residues 869-871, which removes the interaction of V870 with the neighboring ABD, resulted in no detectable actin binding in solution (Xu et al, 2020), suggesting that interactions between neighboring complexes are required to enter a non-transient actin-binding conformation. Cooperative binding was also observed in single-molecule optical trap assays (Arbore et al, 2022; Buckley et al, 2014). In particular, the addition of soluble ABD enhanced the binding lifetimes of surface-bound cadherin-catenin complexes approximately four-fold (Buckley et al, 2014).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Using an improved OT setup and determining the polarity of the filament by measuring the direction of its movement in a separate flow channel containing the pointed (-) end directed motor myosin VI [29], we demonstrated that vinculin itself shows catch bond behavior that is asymmetric: its lifetime bound to F-actin is longer when force is directed towards the pointed (-) end of the actin filament than toward the barbed (+) end [29]. Asymmetric catch bond behavior was also recently reported for aE-catenin alone [35]. We therefore re-measured the forcedependent association of the ternary complex comprising the E-cadherin cytoplasmic domain, b-catenin, and aE-catenin with F-actin (Fig.…”
Section: The Ternary Complex Shows Asymmetric Force-dependent Binding...supporting
confidence: 75%
“…Structural and biochemical studies [36, 42] found direct contacts between actin-bound αE- catenin ABDs, and suggested that these interactions enhance binding between αE-catenin and F-actin. Cooperative binding of αE-catenin to F-actin was also reported in solution [43] and in a biophysical study wherein a single β-catenin/αE-catenin heterodimer formed a short-lived slip bond, but a higher heterodimer surface density enabled the complex to form a directional catch bond with F-actin [35]. Studies from our laboratories likewise indicate that interactions between neighboring cadherin-catenin complexes facilitates F-actin binding under load [18, 30].…”
Section: Resultsmentioning
confidence: 88%